Relatlimab: a novel drug targeting immune checkpoint LAG-3 in melanoma therapy - Su, Jingjing; Fu, Yiting; Cui, Zitong; Abidin, Zain; Yuan, Jingsong; Zhang, Xinmiao; Li, Runmin; Zhao, Chunzhen (Frontiers in Pharmacology, 2024)
Relatlimab is a type of human immunoglobulin G4 monoclonal blocking antibody. It is the world's first Lymphocyte-Activation Gene-3 (LAG-3) inhibitor and the third immune checkpoint inhibitor with clinical application, following PD-1 and CTLA-4.Relatlimab can bind to the LAG-3 receptor which blocks the interaction between LAG-3 and its ligand to reduce LAG-3 pathway-mediated immunosuppression and promote T-cell proliferation, inducing tumor cell death. On March 18, 2022, the U.S.Squibb with nivolumab, under the brand name Opdualag for the treatment of unresectable or metastatic melanoma in adult and pediatric patients aged 12 and older.This study comprehensively describes the mechanism of action and clinical trials of relatlimab and a brief overview of immune checkpoint drugs currently used for the treatment of melanoma.